Specification of individual Slouch muscle progenitors in Drosophila requires sequential Wingless signaling. - Cox, V.T.; Baylies, M.K. (Development, 2005)
The patterning of the Drosophila mesoderm requires Wingless (Wg), one of the founding members of a large family of secreted glycoproteins, the Wnt family. Little is known about how Wg provides patterning information to the mesoderm, which is neither an epithelium nor contains the site of Wg production. By studying specification of muscle founder cells as marked by the lineage-specific transcription factor Slouch, we asked how mesodermal cells interpret the steady flow of Wg. Through the manipulation of place, time and amount of Wg signaling, we have observed that Slouch founder cell cluster II is more sensitive to Wg levels than the other Slouch-positive founder cell clusters. To specify Slouch cluster I, Wg signaling is required to maintain high levels of the myogenic transcriptional regulator Twist. However, to specify cluster II, Wg not only maintains high Twist levels, but also provides a second contribution to activate Slouch expression. This dual requirement for Wg provides a paradigm for understanding how one signaling pathway can act over time to create a diverse array of patterning outcomes.